Clinical and radiographic peri‐implant outcomes of short dental implants placed in posterior jaws of patients with treated generalized aggressive periodontitis: A 3‐year follow‐up study. (1st April 2019) - Akram, Zohaib; Vohra, Fahim; Sheikh, Saeed A.; Albaijan, Refal; Bukhari, Ishfaq A.; Hussain, Mudassir
Abstract: Background: Studies assessing clinical and radiographic peri‐implant parameters around short dental implants (SDIs) in treated generalized aggressive periodontitis (GAgP) patients are scant. Objectives: This 3‐year follow‐up study aimed to compare the clinical peri‐implant and radiographic bone status around SDIs placed in partially edentulous patients treated for GAgP and periodontally healthy patients and to assess the implant success rate between both the groups. Materials and Methods: A total of seven patients clinically diagnosed with GAgP and seven periodontally healthy patients was included in the clinical study. Forty‐eight (29 maxilla; 19 mandible) and 11 (8 maxilla; 3 mandible) SDIs were placed in the GAgP group and healthy group, respectively. Plaque index (PI), bleeding on probing (BOP), probing depth (PD), and clinical attachment level (CAL) were recorded at six sites around all teeth and implants. Marginal bone loss (MBL) was studied incorporating in a specialized software and examined on a calibrated computer display screen with the help of an image analyzer. Patient satisfaction was recorded using a questionnaire sheet that contained questions regarding esthetics and function of the restorations. Results: The implant survival rate after 3 years was 81.25%. BOP and CAL around SDIs of GAgP patients were significantly higher than in periodontally healthy subjects ( P = .01) throughout the follow‐up. CAL around the teeth of GAgP patients was significantly greater during the follow‐up than around the teeth of periodontal healthy subjects ( P = .02). The PI and BOP between the teeth and implants showed no statistical significant difference. The mean PD at teeth was 0.4 mm greater than at implants. Implants showed significantly increased attachment loss than teeth ( P = .01). The overall mean satisfaction of visual analogue scale was 12.8 ± 1.45. Conclusion: This short‐term follow‐up study indicates SDIs remain functionally stable in the posterior jaws of treated GAgP patients.